Epidemiology of Ductal Carcinoma in Situ in Western Australia: Implications for Surgical Margins and Management - Butler-Henderson, Kerryn; Lee, Andy; Lenzo, N.; Price, R. (Springer Japan KK, 2014)
Background: In 2010, the Australian Institute of Health and Welfare published a report examining the characteristics of Australian women diagnosed with ductal carcinoma in situ (DCIS). This study identified the characteristics of women who were diagnosed with DCIS in Western Australia (WA) 1996–2005, and built on a national study by determining the rate of second operation and breast cancer events (BCE) in WA. Methods: A retrospective analysis of data from the WA Cancer Registry and the Hospital Morbidity Database was undertaken. The main outcome measures were histological characteristics, second operation rate, breast cancer events. Results: A total of 1356 cases of DCIS were diagnosed in WA between 1996 and 2005, with a minimum 5-year follow-up. The age-standardised incidence rate in 2005 was 15.4 per 100,000 women. 72 % of patients received breast-conserving therapy for primary treatment, 18 % of patients requiring a second operation to obtain adequate margins and 35 % of patients received postoperative radiotherapy. 17.3 % of cases had a subsequent BCE, with the 5- and 10-year probabilities being 4.36 and 8.27 %, respectively. A BCE was significantly associated with age (p < 0.001), no second operation (p < 0.001) and no radiotherapy (p = 0.049 recurrence, p = 0.043 invasion). Conclusion: This study supports the need to ensure adequate margins during primary surgery for DCIS is obtained to reduce the need for a second operation or the risk of a subsequent BCE. The consideration of mastectomy versus radiotherapy should be made in conjunction with the identified risk factors, specifically age and whether a second operation was performed.